2022
DOI: 10.1097/mou.0000000000001005
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic-guided puncture: a tool or a tale?

Abstract: Purpose of reviewThe puncture technique and site of the puncture can impact the clinical outcome and the development of postoperative adverse events following percutaneous nephrolithotomy (PCNL). The aim of the current review was to discuss the available puncture guidance approaches and outline the potential role of the recently introduced electromagnetic-guided method. Recent findingsThe puncture and PCNL tract establishment is usually performed using fluoroscopic or ultrasound guidance or a combination of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Electromagnetic guided puncture has a high success rate and a short learning curve for beginners (14). To simplify and enhance puncture success, especially for novices, we attempted to perform percutaneous puncture with a navigation system based on deep learning and mixed reality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Electromagnetic guided puncture has a high success rate and a short learning curve for beginners (14). To simplify and enhance puncture success, especially for novices, we attempted to perform percutaneous puncture with a navigation system based on deep learning and mixed reality.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study, Francesco et al reported that three-dimensional mixed reality hologram guidance for percutaneous puncture was safe, that the procedure was highly effective in clinical practice, and that it was associated with a low intraoperative radiation exposure (11). New imaging techniques, such as three-dimensional printing, visual needles, and electromagnetic navigation system, aim to simplify percutaneous puncture and reduce complications (12,13,14). In our study, the navigation system based on deep learning and mixed reality, which could achieve real-time navigation, was applied for the treatment of kidney stones during percutaneous nephrolithotomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning urology, EMN guidance is utilized as a new method for the percutaneous renal puncture. After the selection of the most convenient calyx, a special wire equipped with an electromagnetic tracking sensor is placed via a retrograde flexible ureteroscope [27 ▪ ]. The puncture can be performed under real-time imaging of the orientation and the position of both the needle and the sensor.…”
Section: Electromagnetic-guided Puncturementioning
confidence: 99%